Cardiac rehabilitation in patients with peripheral arterial disease after revascularization. (June 2021) - Sami, Farhad; Ranka, Sagar; Lippmann, Matthew; Weiford, Brian; Hance, Kirk; Whitman, Bob; Wright, Lanecia; Donaldson, Seth; Boyer, Blake; Gupta, Kamal
Objectives: To evaluate safety, feasibility, and benefit of cardiac rehabilitation (CR) in patients with peripheral arterial disease (PAD) who undergo revascularization. Methods: We conducted a prospective, non-randomized, pilot study to assess the feasibility, safety, and benefit of CR in PAD patients after revascularization compared to standard of care (controls). CR feasibility was assessed by the ability to complete 36 sessions. Safety was defined as the absence of adverse cardiovascular events during CR. Quality of life (QoL) assessment was performed using SF-36 form (Medical Outcomes Study 36-Item Short-Form Health Survey) and PAD-specific quality of life questionnaire (VascuQOL6). Other endpoints included incidence of claudication during 6-minute walk test (6MWT), mean distance, and number of laps walked. All outcome data were collected before and after CR completion. Standard statistical tests were used for comparisons. Results: This study enrolled 20 subjects (CR group = 10). Mean age was 60.70 (±7.13) and 63.1 (±9.17) years in CR and controls, respectively ( p -value > 0.05). Fifty percent and 60% were female in CR and control group, respectively. All subjects completed 36 CR sessions without adverse events. The increase in mean distance walked during 6MWT was higher in the CR group compared to control group (63.7 m vs. 10.5 m, p  = 0.043). Change in mean number of laps walked was higher in the CR group (3.5 vs. –1.1; p  < 0.01). Scores on 6 of 8 scales of SF-36 and VascuQOL6 were higher in the CR group, though not statistically significant. Conclusion: CR is safe, feasible, and improves walking ability in ambulatory patients with PAD after arterial revascularization.